If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -9 = 5(x + 3) Reorder the terms: -9 + 4x = 5(x + 3) Reorder the terms: -9 + 4x = 5(3 + x) -9 + 4x = (3 * 5 + x * 5) -9 + 4x = (15 + 5x) Solving -9 + 4x = 15 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -9 + 4x + -5x = 15 + 5x + -5x Combine like terms: 4x + -5x = -1x -9 + -1x = 15 + 5x + -5x Combine like terms: 5x + -5x = 0 -9 + -1x = 15 + 0 -9 + -1x = 15 Add '9' to each side of the equation. -9 + 9 + -1x = 15 + 9 Combine like terms: -9 + 9 = 0 0 + -1x = 15 + 9 -1x = 15 + 9 Combine like terms: 15 + 9 = 24 -1x = 24 Divide each side by '-1'. x = -24 Simplifying x = -24
| 3(4x+12)-14+7=75 | | -6(x+3)=12 | | a-4a=2a | | 3h-4=h+2 | | y+5/11=3 | | 48=-3p | | 2(3+3x)-4=20 | | 7x^2+38x+15= | | 39=5g-9 | | 3(4x+2)=2(4x+50) | | 1-7x+3=-17 | | 45.3*6= | | 1000=2000*(1+x) | | -12-5+11+4-5-13=12 | | -5c+6=-29 | | 14=-(p-8)+2 | | 6x+3=4x-8 | | 1000=x*(1+0,45) | | 3(3a-5)=60 | | 7(1+4x)=147 | | 4z^2-12z+13=0 | | w-15=4 | | 0=1.5x+x^1 | | -1+(-1.5)= | | 6(2x+5)= | | -3(-4x+2)=18 | | 3(10-3x)=120 | | x+1/4=5/8 | | 10-4x=6x-90 | | 0=16t^2-24t-1 | | x-33/7=2/3 | | 0=16t^2+24t+1 |